Literasi Digital Marketing Pada Wirausaha Perempuan Di Sumatera Utara - Erwansyah, Erwansyah; Rini, Endang Sulistya (Yayasan Cita Cendikiawan Al Kharizmi, 2023)
Abstract In digital era, digital marketing is one of the most effective ways to support marketing activities and increase sales. However, there are still many people who do not understand digital marketing, especially among women entrepreneurs in North Sumatra. Although they are accustomed to using social media as a communication medium, this habit must continue to be improved in developing their business marketing strategies. The lack of understanding of women entrepreneurs about digital marketing encourages community service activities to be carried out by delivering socialization and providing training on the use of information and communication technology. From the partner's problems obtained, the solution offered to partners is to provide material related to knowledge of digital marketing concepts and provide skills in the use and optimization of information technology products. The methods used in this activity are lectures, questions and answers, and simulations. The target to be achieved in this community service activity is the implementation of the introduction and optimal utilization of digital marketing in an effort to increase sales for women entrepreneurs in North Sumatra who are members of several women entrepreneurial communities. Keywords: Digital Marketing, Womenpreneurs, Micro, Small and Medium Enterprises Abstrak Di era yang serba digital, digital marketing merupakan salah satu cara paling efektif untuk mendukung kegiatan pemasaran dan meningkatkan penjualan. Walau demikian, masih banyak orang yang belum memahami mengenai digital marketing khususnya di lingkungan wirausaha perempuan di Sumatera Utara.Walaupun mereka sudah terbiasa menggunakan media sosial sebagai media komunikasi tetapi kebiasaan ini harus terus ditingkatkan penggunaannya dalam mengembangkan strategi pemasaran usahanya. Kurangnya pemahaman wirausaha perempuan mengenai digital marketing mendorong untuk dilakukan kegiatan pengabdian kepada masyarakat dengan cara menyampaikan sosialisasi dan memberikan pelatihan mengenai penggunaan teknologi informasi dan komunikasi. Dari permasalahan mitra yang didapatkan maka solusi yang ditawarkan kepada mitra adalah dengan memberikan materi terkait pengetahuan tentang konsep digital marketing dan memberikan keterampilan dalam penggunaan dan optimalisasi produk teknologi informasi. Metode yang digunakan dalam kegiatan ini adalah ceramah, tanya jawab, dan simulasi. Adapun target yang ingin dicapai dalam kegiatan pengabdian kepada masyarakat ini adalah pelaksanaan pengenalan dan pemanfaatan secara optimal digital marketing dalam upaya meningkatkan penjualan bagi wirausaha perempuan di Sumatera Utara yang tergabung dalam beberapa komunitas wirausaha perempuan. Kata kunci: Digital Marketing, Wirausaha Perempuan, Usaha Mikro Kecil Menengah